Risk Assessment Analysis of Hybrid Renewable Energy Systems in Remote Areas: Case Study of Domadgee, Australia - Risky, Muhammad Fahrul (Journal of Power, Energy, and Control, 2024)
This study comprehensively analyses the energy requirements and options for Doomadgee, a remote indigenous community in Australia. Currently, the electricity provider relies on a 2.44 MW diesel power generator, resulting in high operational costs and carbon emissions. This study explores transition options to renewable energy sources to address these challenges while ensuring reliable and cost-effective power supply. This study suggests utilising a 2.4 MW wind energy source, a 1.2 MW solar energy source, and a 4 MW battery storage system that can last 8 hours. This configuration aims to reduce diesel consumption, optimise the internal rate of return (IRR), and establish a sustainable energy mix with low capital expenditure. The wind and solar capacities recommended for Doomadgee also consider seasonal fluctuations, such as wet and dry seasons in energy demand, ensuring efficient power production all year round. The study commences with the development of a risk matrix to determine the hurdle rate. The next step involves conducting ten distinct scenarios to evaluate the investment's financial feasibility, considering various variables such as wind, solar, equipment, and battery storage capacities. Sensitivity analysis also determines the most significant factors impacting financial valuation. This analysis provides valuable insights that can aid in the decision-making process.